CRF modulates glutamate transmission in the central amygdala of naïve and ethanol-dependent rats - Varodayan, Florence P. (Neuropharmacology, 2017)
Corticotropin-releasing factor (CRF) signaling in the central nucleus of the amygdala (CeA) is hypothesized to drive the development of alcohol dependence, as it regulates ethanol intake and several anxiogenic behaviors linked to withdrawal. Excitatory glutamatergic neurotransmission contributes to alcohol reinforcement, tolerance and dependence. Therefore, in this study we used in vitro slice electrophysiology to investigate the effects of CRF and its receptor subtype (CRF(1) and CRF(2)) antagonists on both evoked and spontaneous action potential-independent glutamatergic transmission in the CeA of naive and ethanol-dependent Sprague-Dawley rats. We found that CRF (25–200 nM) concentration-dependently diminished evoked compound excitatory postsynaptic potentials (EPSPs), but increased miniature excitatory postsynaptic current (mEPSC) frequencies similarly in CeA neurons of both naïve and ethanol-dependent rats, indicating reduced evoked glutamatergic responses and enhanced vesicular glutamate release, respectively. This CRF-induced vesicular glutamate release was prevented by the CRF(1/2) antagonist (Astressin B) and the CRF(1) antagonist (R121919), but not by the CRF(2) antagonist (Astressin 2B). Similarly, CRF’s effects on evoked glutamatergic responses were completely blocked by CRF(1) antagonism, but only slightly decreased in the presence of the CRF(2) antagonist. Moreover, CRF(1) antagonism reveals a tonic facilitation of vesicular glutamate, whereas the CRF(2) antagonism revealed a tonic inhibition of vesicular glutamate release. Collectively our data show that CRF primarily acts at presynaptic CRF(1) to produce opposite effects on CeA evoked and spontaneous glutamatergic release and that the CRF system modulates CeA glutamatergic synapses throughout the development of alcohol dependence.